2005
DOI: 10.1261/rna.7269305
|View full text |Cite
|
Sign up to set email alerts
|

Transfer-messenger RNA unfolds as it transits the ribosome

Abstract: In bacteria, translation of mRNAs lacking stop codons produces truncated polypeptides and traps ribosomes in unproductive complexes. Potentially harmful truncated proteins are tagged with short peptides encoded by the mRNA-like domain of tmRNA and targeted for digestion by housekeeping proteases. We show that altered Escherichia coli transfer-messenger RNAs (tmRNAs) produce in vivo fusion proteins with peptide tags that extend far beyond the conventional termination signal of the wild-type tmRNA. Regions of tm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…The second state is the state after the release of EF-Tu, in which tmRNA has moved into the A site. The resulting density map, at 12-Å resolution, shows the tmRNA to be largely unstructured, in agreement with predictions from recent biochemical findings of Wower et al (17).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The second state is the state after the release of EF-Tu, in which tmRNA has moved into the A site. The resulting density map, at 12-Å resolution, shows the tmRNA to be largely unstructured, in agreement with predictions from recent biochemical findings of Wower et al (17).…”
supporting
confidence: 89%
“…Another unsolved problem is the fate of tmRNA in the accommodated state. Wower et al (17) concluded from biochemical data that the tmRNA is partially unstructured after release of EF-Tu from the ribosome and accommodation of TLD, after insertion of the ORF into the mRNA channel. Again, a confirmation of this result by structural methods has thus far been missing, and it is as yet unclear how the binding or release of the SmpBs is coordinated with the unraveling of tmRNA.…”
mentioning
confidence: 99%
“…5A). As there are different structural intermediates during the folding (49) and function (19,50) of tmRNA, we wanted to confirm that ACAs in the single-strand region of the structure proposed previously by Zwieb et al (57) are more accessible to MazF cleavage than are double-strand ACAs.…”
Section: Correlation Of Mazf Homologues and The Absence Of Acas In Tmmentioning
confidence: 84%
“…In addition, the putative unwinding of pseudo-knot structures PK2-PK4 (Kaur et al 2006) would require a significant input of free energy from a yet unidentified source. The observation that replacement of the stop codons at the end of the ORF of tmRNA with sense codons results in the synthesis of abnormally long-tag peptides (Wower et al 2005) shows that unwinding of the tmRNA secondary in the PK2-PK4 can take place. However, in this latter case the free energy for unwinding is provided by protein elongation, which supports the present and previous conclusions (Ivanov et al 2002;Shpanchenko et al 2005) that the putative unwinding of tmRNA takes place at a much later stage of trans-translation than tmRNA accommodation in the A site.…”
Section: Discussionmentioning
confidence: 99%